The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1186/s13048-017-0303-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a single 20 mg dose of letrozole on ovarian function post dominant follicle selection: an exploratory randomized controlled trial

Abstract: BackgroundOur objective was to explore the impact of a single dose of an aromatase inhibitor (letrozole) administered at defined times of the follicular phase or immediately after ovulation on dominant follicle development, luteogenesis and new follicle wave emergence.MethodsA prospective pilot study using a randomized complete block, controlled, open label design was conducted at an academic clinical research center. Forty-five healthy, female volunteers (25.5 ± 0.9 years, BMI 25.0 ± 0.6 kg/m2) who had not ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These vesicles are released by tumor cells and most other cells types of the TME [ 159 , 160 ]. They mediate the transfer of proteins, lipids, and nucleic acids such as DNAs, mRNAs, and miRNAs between tumor and stroma [ 161 ].…”
Section: Other Components Of the Ovarian Tmementioning
confidence: 99%
See 1 more Smart Citation
“…These vesicles are released by tumor cells and most other cells types of the TME [ 159 , 160 ]. They mediate the transfer of proteins, lipids, and nucleic acids such as DNAs, mRNAs, and miRNAs between tumor and stroma [ 161 ].…”
Section: Other Components Of the Ovarian Tmementioning
confidence: 99%
“…EVs range from 30 to 150 nm, whereas microvesicular bodies (MVBs) are 100 nm to 1 µm [ 162 ]. EVs carry molecules such as CD24, and epithelial cell adhesion molecule (EPCAM1), which directly regulate cancer-cell migration, proteases (MMP2, MMP9), which promote ECM degradation and cancer invasiveness [ 160 , 163 , 164 ], or EV-associated mRNAs, such as miR21, which may induce resistance to paclitaxel [ 163 , 165 , 166 ].…”
Section: Other Components Of the Ovarian Tmementioning
confidence: 99%
“…Allaway et al found that a single dose of 20 mg of letrozole could lower the E 2 levels while increasing the levels of luteinizing hormone (LH) and follicle stimulating hormone (FSH) level when the diameter of dominant ovarian follicles reached 12 mm or 18 mm after ovulation [ 21 ]. However, the changing levels of hormones did not result in the disappearance of dominant follicles, and in this study, the use of letrozole at E 2 peak levels could quickly lower E 2 levels to effectively prevent OHSS [ 21 ]. However, the development of the dominant ovarian follicle was not be affected and the lowered E 2 level was beneficial for embryo transfer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the changing levels of hormones did not result in the disappearance of dominant follicles, and in this study, the use of letrozole at E 2 peak levels could quickly lower E 2 levels to effectively prevent OHSS [ 21 ]. However, the development of the dominant ovarian follicle was not be affected and the lowered E 2 level was beneficial for embryo transfer [ 21 ]. Another study also indicated that the co-administration of letrozole and gonadotropin in the IVF cycle could increase the expression of integrin in the endometrium and increased endometrial receptivity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire to survey was performed in breast cancer patients younger than 35 years and 8% of patients rejected to receive chemotherapy because of worried about reducing their fertility [14]. GnRHa can protect ovarian function during chemotherapy for HR-negative breast cancer patients [15]. More important for clinicians and patients were to understand the state of ovarian function and protect their ovarian function.…”
Section: Introductionmentioning
confidence: 99%